2023
DOI: 10.1073/pnas.2216941120
|View full text |Cite
|
Sign up to set email alerts
|

Propionate exerts neuroprotective and neuroregenerative effects in the peripheral nervous system

Abstract: In inflammatory neuropathies, oxidative stress results in neuronal and Schwann cell (SC) death promoting early neurodegeneration and clinical disability. Treatment with the short-chain fatty acid propionate showed a significant immunoregulatory and neuroprotective effect in multiple sclerosis patients. Similar effects have been described for patients with chronic inflammatory demyelinating polyneuropathy (CIDP). Therefore, Schwann cell’s survival and dorsal root ganglia (DRG) outgrowth were evaluated in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Our results suggest that more attention needs to be paid to the progression of CIDP. Also, further studies are needed to show whether these patients benefit from intensified immunotherapy or potential neuroprotective substances [19] to achieve long‐term stability.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that more attention needs to be paid to the progression of CIDP. Also, further studies are needed to show whether these patients benefit from intensified immunotherapy or potential neuroprotective substances [19] to achieve long‐term stability.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the YCFAGSC medium used for culturing the four bacteria is rich in vitamins (Duncan et al, 2002) that might promote brain health (Kennedy, 2016), and became a major confounder within our study design. Notably, the culture medium was also rich in the SCFA propionate (see figure 8), which has been recently suggested to exert neuroprotective effects (e.g., Filippone et al, 2020;Hou et al, 2021;Grüter et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the culture medium was also rich in the SCFA propionate (see figure 8), which has been recently suggested to exert neuroprotective effects ( e.g. , Filippone et al ., 2020; Hou et al ., 2021; Grüter et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Data published suggest that microbiome transplantation from lean to obese mice may alleviate pain and increases nerve survival and/or growth via short chain fatty acids (e.g., butyrate) (Bonomo et al, 2020). Recently, in-vitro studies demonstrated a potential antioxidative and neurodegenerative effect of propionate in the peripheral nerve system suggesting that propionate could be used in immune-mediated neuropathies (Grüter et al, 2023). Some SCFA have been demonstrated to cross the blood brain barrier in rats (Oldendorf, 1973) and in humans (Bachmann et al, 1979), possibly due to high expression of their transporter, monocarboxylate transporters (MCTs) in blood cells and astrocytes (Bachmann et al, 1979;Dalile et al, 2019).…”
Section: Scfa and Neuropathymentioning
confidence: 99%